Busting out stress: a case study of stress management in Citibank Berhad / Nur Amalina Muzaffar - Muzaffar, Nur Amalina (2012)
Stress is a normal physical response to events that make you feel threatened or upset your balance in some way. The body’s defenses kick into high gear in a rapid, automatic process known as the “fight or-flight” reaction or stress response when someone in the sense of danger whether it is real or not. Stress response is the body’s way of protecting ourselves. When it is working properly, it helps us to stay focused, energetic, and alert as well as helps us to rise to meet challenges. However, beyond a certain point, stress stops being helpful and can caused major damage to our health, mood, productivity, relationships as well as our quality of life. The purpose of this study was made to analyzed regarding on the stress management of employee in Citibank Berhad. This study will look at some of the ways on managing stress to avoid it from turning into a worst problem. The ultimate goal of managing stress is a balanced life, time for work, relationships, relaxation and enjoying your life plus holding up under pressure and meet challenges head on. At the end of the study, it will come out with recommendations or suggestions on stress management so that employees are not pressured with stress and able to work in a less stressed environment. This study was made based on primary and secondary data. Informal interview was conducted and stress management data was obtained during the stress management talk held in Citibank. In the future, this study can be used as a reference or guide for Citibank Berhad in ways of managing stress, to improve as well as adding more programs for employees in terms of stress management.